An osteometric and 3D analysis of the atlanto‐occipital joint: An initial screening method to exclude crania and atlases in commingled remains. Issue 3 (9th November 2021) - Cappella, Annalisa; Affatato, Luciana; Gibelli, Daniele; Mazzarelli, Debora; Zago, Matteo; Dolci, Claudia; Sforza, Chiarella; Cattaneo, Cristina
Abstract: Objectives: The anatomical features of the atlanto‐occipital joint can be potentially useful in re‐associating or excluding crania to atlases in commingled remains. This study investigated whether linear measurements and the 3‐dimensional (3D) surface of occipital condyles and articular facets of atlases can represent valid insights for this purpose. Methods: The variations among eight corresponding linear distances were analyzed in a sample of 150 individuals through six supervised machine learning techniques attempting to develop classifiers able to identify elements belonging to the same individual. Furthermore, a 3D analysis was conducted on the articular surfaces through superimpositions of 3D models of corresponding and non‐corresponding crania and atlases obtained by using respectively stereophotogrammetry and laser scanning. This analysis investigated differences in terms of point‐to‐point distances (Root Mean Square, RMS) of superimposed 3D surfaces. Results: None of the six machine learning techniques were able to correctly detect a satisfying percentage of correspondent pairs in the overall sample by using the linear variables. The 3D analysis of the articular surfaces found RMS values over 0.53 mm only for superimposed non‐corresponding surfaces, which sets a threshold value to identify 32% of incorrect pairs. Discussion: The re‐association of cranium to atlas proved to be challenging and hardly possible when considering only metric variables. However, the 3D geometry of the articular surfaces represents a valid variable for this purpose and 3D analyses pave the way for an initial exclusion of incorrect re‐associations, thus should not be considered as a re‐association method per se, but as an exclusionary screening technique. Abstract : Selection of the ROI from the superior face of atlas obtained with the VAM software. In the blue panel is depicted the over 200 points positioned in the articular surface contour in order to select the area of interest. The red panel shows the final representation of the selected area of interest: the superior articular surfaces of atlas remaining in their original distance and 3D orientation.